2022
DOI: 10.3390/nano12060941
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Toxicity of Polystyrene Nano- and Microplastics Alone and in Combination with Benzo(a)pyrene in Brine Shrimp Larvae and Zebrafish Embryos

Abstract: The occurrence of nanoplastics (NPs) and microplastics (MPs) in aquatic ecosystems and their capacity to sorb hydrophobic pollutants is nowadays an issue of great concern. This study aimed to assess the potential bioavailability and acute toxicity of polystyrene (PS) NPs (50 and 500 nm) and of MPs (4.5 µm), alone and with sorbed benzo(a)pyrene (B(a)P), in the embryo/larval stages of brine shrimps and zebrafish. Exposure to pristine plastics up to 50.1 mg PS/L did not cause significant impact on brine shrimp su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The rate of nauplii mortality increased with the exposure concentration, reaching >70% at 100 mg L −1 , 50–60% at 50 mg L −1 , 30–35% at 5 mg L −1 , and <20% at 0.5 mg L −1 for all types of nanoplastics. These results agreed with previous studies that showed increased mortality (LC 50 40.95 mg L −1 ) of Artemia exposed to higher concentrations (1–100 μg mL −1 ) of PP-MPs 44 and PS-NPs (5–100 μg mL −1 ), 45 as well as PS-NH 2 (100 μg mL −1 ) 22 and PS-NH 2 (10 μg mL −1 ) for 48 h. 6 However, some studies reported no significant effects of MPs on the survival of different brine shrimp species. 23,27,46 This indicates that the size of M/NPs influences the ingestion, bioaccumulation, and survival of brine shrimp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The rate of nauplii mortality increased with the exposure concentration, reaching >70% at 100 mg L −1 , 50–60% at 50 mg L −1 , 30–35% at 5 mg L −1 , and <20% at 0.5 mg L −1 for all types of nanoplastics. These results agreed with previous studies that showed increased mortality (LC 50 40.95 mg L −1 ) of Artemia exposed to higher concentrations (1–100 μg mL −1 ) of PP-MPs 44 and PS-NPs (5–100 μg mL −1 ), 45 as well as PS-NH 2 (100 μg mL −1 ) 22 and PS-NH 2 (10 μg mL −1 ) for 48 h. 6 However, some studies reported no significant effects of MPs on the survival of different brine shrimp species. 23,27,46 This indicates that the size of M/NPs influences the ingestion, bioaccumulation, and survival of brine shrimp.…”
Section: Discussionsupporting
confidence: 93%
“…49) and 100 mg L −1 PS-NH 2 . 22 Nanoplastics accumulated in the gut and other organs of the nauplii in a concentration-dependent manner (Fig. S1 †) with PS-NPs showing the highest bioaccumulation among the three types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature has generally signaled sublethal effects related to exposure to polystyrene even at different concentrations and sizes (6-10 µm at a concentration of 2 mg/L) [66][67][68]. Lethal effects have been observed with the use of particles (10 µm) of polyethylene (which, to date, seems to be the most toxic type of plastic in the short term [69]) or nanoparticles for chronic exposure (14 d) to a concentration of 20-50 µg/mL [70,71]. Again, further studies will have to be performed in order to assess the actual exposure conditions of zooplankton in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of 24 h post hatching (hph) were harvested and selected for the test under a stereoscopic microscope (Nikon smz800, Tokyo, Japan). Larvae immobilization at 24 and 48 h of exposure was used as a criterion for acute toxicity [26]. At least 5 individuals were transferred and maintained for 48 h in each well of the 24-well polystyrene microplates containing 2 mL of exposure medium.…”
Section: Methodsmentioning
confidence: 99%